2021
DOI: 10.3390/cells10020210
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Prevents Disease Progression of Nonalcoholic Steatohepatitis through Modulating Multiple Pathways

Abstract: The disease progression of nonalcoholic fatty liver disease (NAFLD) from simple steatosis (NAFL) to nonalcoholic steatohepatitis (NASH) is driven by multiple factors. Berberine (BBR) is an ancient Chinese medicine and has various beneficial effects on metabolic diseases, including NAFLD/NASH. However, the underlying mechanisms remain incompletely understood due to the limitation of the NASH animal models used. Methods: A high-fat and high-fructose diet-induced mouse model of NAFLD, the best available preclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…Previous studies have indicated that the direct beneficial effects of BBR involving modulation of the expression of multiple genes involved in HSC activation, cholangiocyte proliferation and liver fibrosis are linked to the downregulation of two important ribonucleotide molecules that promote liver fibrosis progression: microRNA34a and long noncoding RNA H19. ( Wang et al, 2021 ). Another commonly reported mechanism is the induction of HSC cycle arrest in G1 phase, which inhibits HSC activation and prevents liver fibrosis.…”
Section: Anti-fibrosis Effects Of Berberine In the Livermentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that the direct beneficial effects of BBR involving modulation of the expression of multiple genes involved in HSC activation, cholangiocyte proliferation and liver fibrosis are linked to the downregulation of two important ribonucleotide molecules that promote liver fibrosis progression: microRNA34a and long noncoding RNA H19. ( Wang et al, 2021 ). Another commonly reported mechanism is the induction of HSC cycle arrest in G1 phase, which inhibits HSC activation and prevents liver fibrosis.…”
Section: Anti-fibrosis Effects Of Berberine In the Livermentioning
confidence: 99%
“…BBR could also significantly reduce hepatic lipid accumulation by modulating fatty acid synthesis and metabolism to prevent the progression of non-alcoholic steatohepatitis and liver fibrosis. ( Wang et al, 2021 ). Several latent mechanisms, such as oxidative stress ( Zhang BJ.…”
Section: Berberine Alleviates Liver Fibrosis By Modifying Lipid Metab...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this study also found that the plasma levels of conjugated primary BAs (TCA and GCA) efficiently discriminate NASH status independent of other confounding factors such as obesity and insulin resistance [ 81 ]. Our recent studies also showed that serum levels of TCA and TβMCA were markedly increased in high-fat diet and high-sugar water-induced NASH mouse models [ 82 ]. TCA-induced activation of S1PR2 is involved in cholangiocyte proliferation and hepatic fibrosis [ 83 ].…”
Section: Gut–liver Axis In Nafldmentioning
confidence: 99%
“…In addition, berberine can also regulate liver TG synthesis and hepatic steatosis through the activation of AMPK-SREBP-1c-SCD1 pathway both in HFD mice and in HepG2/ AML12 cells exposed to high glucose and palmitic acid [ 125 ]. In conclusion, berberine can not only reduce hepatic lipid accumulation by modulating fatty acid synthesis and metabolism, but also restore the bile acid homeostasis [ 126 ]. Furthermore, it markedly inhibits inflammation by reducing immune cell infiltration, neutrophil activation and inflammatory gene expression.…”
Section: Effects and Mechanisms Of Commonly Used Single Herb Drugs In Tcm On Nafldmentioning
confidence: 99%